Why we broke up - Handler, Daniel; Kalman, Maira (New York Little, Brown, 2011)
Sixteen-year-old Min Green writes a letter to Ed Slaterton in which she breaks up with him, documenting their relationship and how items in the accompanying box, from bottle caps to a cookbook, foretell the end.
Keywords: Dating (Social customs) -- Fiction; Souvenirs (Keepsakes) -- Fiction; Letters -- Fiction